Pain Resolving in Addiction and Recovery - Alan Kim-Lok Oh; Puteri Hayati Megat Ahmad; Ferlis bin Bullare Bahari; Peter Voo (Grounded Theory Review: An International Journal, 2016)
The aim of this study is to develop a classic grounded theory about how addicts resolve their pain during addiction and recovery. Interviews and observations were analyzed and secondary analyses were carried out. Pain emerged as the main concern with pain resolving as the emergent pattern of behavior through which they deal with this concern. Pain resolving is a two-stage basic social psychological process of becoming where their identity is formed based on how they resolve their pain. This process of becoming is progressive over time. These two stages are instantaneous pain relieving and honesting. Trapped in instantaneous pain relieving leads an addict to become a worthless person while continuous life-long implementing of honesting brings the addict towards becoming a fully functioning person. Instantaneous pain relieving and honesting account for the patterns of behavior in resolving pain when an addict is in addiction and during the recovering process respectively.